Mini implant orthodontic sebagai penjangkaran pada perawatan maloklusi kelas II skeletal dengan protrusi berat Mini implant orthodontic as an anchorage in skeletal class II malocclusion treatment with severe dental protrusion - Maureen Antolis; Haru Setyo Anggani (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2021)
Pendahuluan: Maloklusi kelas II skeletal memiliki gambaran morfologis yang khas, antara lain adalah protrusi gigi anterior atas, serta profil skeletal dan jaringan lunak cembung. Penatalaksanaan yang cermat terutama penjangkaran, diperlukan agar perawatan ortodonti berhasil, guna mengurangi derajat protrusi gigi anterior atas serta perbaikan profil. Tujuan laporan kasus ini menyampaikan keberhasilan mini implant orthodontic sebagai penjangkaran pada perawatan maloklusi kelas II skeletal dengan protrusi berat.Laporan kasus: Kasus pasien perempuan usia 22 tahun 2 bulan dengan maloklusi kelas II skeletal, yang memiliki profil cembung, mandibula retrognatis, tipe wajah dolichofacial, jarak gigit besar, dengan riwayat rhinitis. Perawatan preadjusted edgewise dilakukan setelah ekstraksi kedua gigi premolar pertama atas yang diikuti dengan pemasangan mini implant orthodontic sebagai penjangkaran. Total waktu perawatan adalah 38 bulan. Jarak dan tumpang gigit normal berhasil dicapai pada akhir perawatan, adapun profil wajah pasien menunjukkan perubahan yang cukup bermakna. Simpulan: Perawatan ortodonti dengan penjangkaran mini implant orthodontic efektif dalam penatalaksanaan pasien pada maloklusi kelas II skeletal dengan protrusi berat. Kata kunci: Mini implant orthodontic, maloklusi kelas II skeletal, protrusi gigi.   ABSTRACT Introduction: Skeletal Class II malocclusion has characteristic morphological features, including the protrusion of the upper anterior teeth and a skeletal profile and convex soft tissue. Careful management, especially anchoring, is necessary for successful orthodontic treatment to reduce the degree of protrusion of the upper anterior teeth and improve the profile. This case report was aimed to address the success of orthodontic mini-implants as anchoring in the treatment of severe protrusion of skeletal Class II malocclusion. Case report: A 22 years two months old female patient with skeletal Class II malocclusion, who had a convex profile, retrognathic mandible, dolichofacial face type, large bite distance, with a history of rhinitis. The preadjusted edgewise treatment was performed after extraction of the two upper first premolars followed by orthodontic mini implant placement as anchors. The total treatment time was 38 months. Normal bite distance and overlap were achieved at the end of treatment, while the patient's facial profile showed significant changes. Conclusion: Orthodontic treatment with orthodontic mini implant anchoring is effective in the management of patients in skeletal Class II malocclusion with severe protrusion. Keywords: Mini implant orthodontic, skeletal class II malocclusion, dental protrusion.